Performance Management Model of Sustainable Safe Production at Deep Mill Level Zone PT. Freeport Indonesia - Tanoto, Eko Wahyu; Syarief, Rizal; Indrawan, Dikky (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
One of the mine expansions that is expected to accelerate the production rate of PT Freeport Indonesia is the Deep Mill Level Zone (DMLZ) mine. The block caving mining method used at the DMLZ mine results in higher productivity levels at lower operating costs but requires ongoing equipment maintenance. This research aims to describe the factors and criteria that determine the production process, find a performance management model, and find the right strategic priorities to increase productivity at DMLZ mine. We analysed the condition of the maintenance management system at the DMLZ mine to find solutions and strategies so that equipment maintenance could be managed effectively. Sustainable Safe Production performance management is developed based on the Balanced Scorecard (BSC) approach combined with the Analytical Network Process (ANP), which is expected to determine the priority of solutions and strategies based on predetermined criteria and indicators. This performance management model considers six perspectives: finance, customers, production, safety, internal business processes, and learning and growth processes as benchmarks in measuring performance. We explained the determination of priority strategies that can be done to achieve three goals in sustainable safe production management: achieving production targets, safe and healthy mining processes, and achieving operational cost-effectiveness. Keywords: analytical network process (ANP), balanced scorecard (BSC), performance management, safe production, sustainable production